(untitled) (Journal of the College of Basic Education, 2023)
On the bridges of communication between East and west in the field of Sufism and female guardian ship in Africa in particular ;by tracing the course of this phenomenon and controlling the most important temporal articulations and defining historical moments BY highlighting the of this movement in bridging the relationship between the East and the Westin the field of the mysticism and the sciences of the inner and outer. We have shown how this experience is unique and of a special nature. perhaps due to the influence of the geographical and historical factor. And we touched the issue of the relationship between the phenomenon of women s guardianship and society .And we showed how the different segments and groups of society interacted ;including youth ;women the general public and elites .And where are the representations of this manifested through practices ;believe and criticism?. F. how necessary is it to adopt a local anthropological approach and move from the stage of assimilation to the stage of transgression .establishment and dual criticism?